2006
DOI: 10.3748/wjg.v12.i27.4406
|View full text |Cite
|
Sign up to set email alerts
|

Isolated antibody to hepatitis B core antigen in patients with chronic hepatitis C virus infection

Abstract: Isolated anti-HBc alone is common in Saudi patients with chronic HCV infection, and is significantly more common in those with CAH than those with cirrhosis. Therefore, a screening strategy that only tests for HBsAg and anti-HBs in these patients will miss a large number of individuals with isolated anti-HBc, who may be potentially infectious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
6
18
1
Order By: Relevance
“…A significant association was found between the presence of HBV DNA and anti-HCV positivity. In agreement with our results, studies by Jilg et al [44] and Helmy et al [45] revealed a high correlation between anti-HCV and hepatitis B core antibodies. Because HBV and HCV have similar transmission models, co-infection of both viruses is expected to be common.…”
Section: Discussionsupporting
confidence: 94%
“…A significant association was found between the presence of HBV DNA and anti-HCV positivity. In agreement with our results, studies by Jilg et al [44] and Helmy et al [45] revealed a high correlation between anti-HCV and hepatitis B core antibodies. Because HBV and HCV have similar transmission models, co-infection of both viruses is expected to be common.…”
Section: Discussionsupporting
confidence: 94%
“…Serologic detection of hepatitis B core antibodies is common in hepatitis B surface antigen-negative patients with chronic hepatitis C. 23 In agreement with our results, studies by Helmy et al 28 and Jilg et al 29 found a high correlation between anti-HCV and hepatitis B core antibodies. Because HBV and HCV have similar transmission models, coinfection of both viruses is expected to be prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…Although the seroprevalence of isolated anti-HBc in blood donors is 2% to 5%, the rates are significantly higher, ranging from 18.6% to 71%, among patients with chronic hepatitis C [1416]. Two separate studies done in Saudi Arabia detected HBV DNA in 15.8% and 22.5% of HCV patients with isolated anti-HBc [14, 15]. …”
Section: Epidemiology Of Hbv/hcv Coinfectionmentioning
confidence: 99%